Tashmim Al’ab Lughawiyah Min Al-Kalimat Al-Indunisiyah Dzatu Aslin ‘Arabi Fi Qamus KBBI - Nawafie Kholief; Hadil Ismail Hasan; Yusta Rizaldi (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
This study aims to find out how to design language games for learning Arabic, through Indonesian vocabulary derived from Arabic in a large Indonesian dictionary, from the letters J to Q. Namely with the translation of the vocabulary.The research method used is the Descriptive Analysis method, by describing and analyzing Indonesian words originating from Arabic in a large Indonesian dictionary, from letters J to Q. Then using these words in designing language games for learning Arabic.The results of this study prove that in the big Indonesian dictionary there are Indonesian vocabulary originating from Arabic from the letter J to Q, the number of vocabulary, which then the vocabulary is divided into four parts according to the meaning of meaning and shape in Indonesian, namely the vocabulary that contains the same meaning as Arabic, that experiences narrowing of meaning in Indonesian, that experiences the expansion of meaning in Indonesian, that has changed in total meaning in Indonesian. This study also concluded that the vocabulary can be used as a design of language games by placing vocabulary based on language skills. Here's the division of the game: the game in listening skills, in speaking skills, in reading skills, and in writing skills.